FLUCTUATION IN CALCIUM LEVELS IN THE EXOSKELETON, MUSCLE AND HAEMOLYM'PH OF PENAEUS INDICUS, CULTIVATED IN A BRACKI8HWATER POND - Rao, P Vedavyasa; Diwan, A D; Kakati, V S (Indian Journal of Fisheries, 2011)
The calcium content in the exoskeleton of Penaeus indicus cultivated in abrackishwaterpond was found between 4 and 15%, which was low compared toother crustaceans. The haemolymph calcium was observed always at a higher levelthan the calcium in the pond water. Calcium content of pond water and haemolymphshowed a direct relationship wiith the salinity. Relatively high levels ofcalcium in muscle and low levels in exoskeleton were observed in June, the probablereasons for this abrupt fall in the values are discussed.